2019
DOI: 10.1002/jimd.12042
|View full text |Cite
|
Sign up to set email alerts
|

The cholic acid extension study in Zellweger spectrum disorders: Results and implications for therapy

Abstract: Introduction Currently, no therapies are available for Zellweger spectrum disorders (ZSDs), a group of genetic metabolic disorders characterised by a deficiency of functional peroxisomes. In a previous study, we showed that oral cholic acid (CA) treatment can suppress bile acid synthesis in ZSD patients and, thereby, decrease plasma levels of toxic C27‐bile acid intermediates, one of the biochemical abnormalities in these patients. However, no effect on clinically relevant outcome measures could be observed af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
0
9
2
1
Order By: Relevance
“…It was hypothesis that cholic acid therapy could prevent disease progression and progression of liver disease. However, short‐ and long‐term follow‐up showed, besides significant increase in weight, no improvement of clinical symptoms or liver phenotype . Long‐term follow‐up did show stabilization of liver function/enzymes .…”
Section: Discussionmentioning
confidence: 89%
“…It was hypothesis that cholic acid therapy could prevent disease progression and progression of liver disease. However, short‐ and long‐term follow‐up showed, besides significant increase in weight, no improvement of clinical symptoms or liver phenotype . Long‐term follow‐up did show stabilization of liver function/enzymes .…”
Section: Discussionmentioning
confidence: 89%
“…While some studies suggest a beneficial effect of DHA supplementation in patients with Zellweger spectrum disorders, a randomized double-blind placebo-controlled trial showed no improvement of visual function and growth [ 21 , 22 ]. Similarly, despite FDA approval, studies surrounding cholic acid supplementation have not demonstrated improved growth and development or reduced urinary excretion of toxic intermediates in these patients [ 23 , 24 ]. Additional research is needed to evaluate efficacy of DHA and cholic acid as combination therapy for IRD.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormally elevated bile acid intermediates are thought to be toxic for the brain [ 8 , 9 ], potentially causing neurological disease. Despite the paucity of clinical evidence, bile acid supplementation with 5–15 mg/kg cholic acid (CA) for the treatment of different types of BASDs has been available for many years [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. It has been hypothesized that cholic acid supplementation decreases endogenous bile acid production, stimulates bile secretion, and improves bile flow and micellar solubilization, thereby improving the biochemical profile and potentially slowing down disease progression [ 2 , 7 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%